Iannis Xenakis (1922-2001): an examination of the implementation of stochastic procedures in selected compositions - Du Toit, Pierre Johannes (Stellenbosch : University of Stellenbosch, 2009)
Thesis (MMus (Music))--University of Stellenbosch, 2009.